Antimicrobial peptide production with Corynebacterium glutamicum on lignocellulosic side streams - Daniel Waldschitz; Mark-Richard Neudert; Jakob Kitzmüller; Jae Hwi Bong; Yannick Bus; Eva Maria Karner; Peter Sinner; Oliver Spadiut (Biotechnology for Biofuels and Bioproducts)
Abstract Background Biorefineries usually focus on the production of low-value commodities, such as bioethanol, platform chemicals or single cell protein. Shifting production to bioactive compounds, such as antimicrobial peptides, could provide an opportunity to increase the economic viability of biorefineries. Results Recombinant production of the antimicrobial peptide pediocin PA-1 in Corynebacterium glutamicum was transferred from yeast extract-based media to minimal media based on lignocellulosic spent sulfite liquor. Induced batch, fed batch, and extended batch process modes were compared for highest pediocin PA-1 production. Conclusion For pediocin PA-1 production on lignocellulosic residues, extended batch cultivation was identified as the optimal process mode, producing up to $$\simeq$$ ≃  104 mg/L active pediocin PA-1. Moreover, the production of pediocin PA-1 on this sustainable second generation resource exceeded its state-of-the-art production on yeast extract-based media $$\simeq$$ ≃  1.5-fold.